Peningkatan Keterampilan Menulis Teks Berita melalui Model Pembelajaran Discovery Learning Berbantuan Media Flipbook pada Siswa Kelas VII-C MTsN 2 Jember - Lusiana Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The implementation of news writing instruction using the discovery learning model supplemented by a flipbook aims to improve the news writing skills of seventh-grade students in Class VII-C at MTsN 2 Jember. This approach was chosen because the students’ writing skills remain inadequate, particularly in identifying key elements of news texts specifically the “why” and “how” components, which are often mistakenly considered nearly identical. Students still struggle to distinguish between the news lead and the news body. The majority of students have not yet written news texts in accordance with proper linguistic conventions. The research procedure used in this study is classroom action research (PTK). This study employs Kurt Lewin’s classroom action research (PTK) model, which consists of four steps: planning, implementation, observation, and reflection. Data collection in this study utilized observation, interviews, documentation, and tests. The results of this study indicate an improvement in the news writing skills of seventh-grade students in Class VII-C at MTsN 2 Jember. In the pre-cycle, the average score for students’ news text writing was 60.4 with a pass rate of 24%; the average score was 74.2 with a pass rate of 64% in Cycle I (completed); and the average score was 84.6 with a pass rate of 88% in Cycle II.
Approved by Teddy
Keywords: Classroom action research; Discovery learning; Flipbook.; News articles; Writing skills